'Amphibians': media figures on social networks and traditional media in Israel. Issue 3 (4th May 2021) - Laor, Tal
ABSTRACT: Digital platforms have become a major tool for media figures. The Internet offers the media essential tools, most notably authentic and accessible sources of information and the absence of censorship. Digital media provides media personalities with a platform that is free and fast where they can express themselves freely without 'gatekeepers.' Drawing on Deuze's five-dimensional model of journalism, this article shows that for the content transfer platform, the network is characterised by a young audience, leading to more consumer confidence due to its authentic nature. It also found that platform selection relates directly to content and that media people use the network to promote agendas. In addition, their influence on social networks is greater because they are bi-directional and allow for audience reaction. As for the media figure's personality, it was found that the success of media figures does not involve the quality of the content but the admiration of the audience. In addition, it emerged from the interviews that technological determinism affects media figure activities such that 'the medium is the message' – type of media dictates choice of the content transfer platform, content, and media figure personality.